Feasibility and usefulness of postoperative mobilization goals in the enhanced recovery after surgery (ERAS®) clinical pathway for elective colorectal surgery - Wiesenberger, Rico; Müller, Julian; Kaufmann, Mario; Weiß, Christel; Ghezel-Ahmadi, David; Hardt, Julia; Reißfelder, Christoph; Herrle, Florian (Langenbeck's archives of surgery, 2024)
Purpose: Despite mobilization is highly recommended in the ERAS® colorectal guideline, studies suggest that more than half of patients don’t reach the daily goal of 360 min out of bed. However, data used to quantify mobilization are predominantly based on self-assessments, for which the accuracy is uncertain. This study aims to accurately measure postoperative mobilization in ERAS®-patients by validated motion data from body sensors. Methods: ERAS®-patients with elective bowel resections were eligible. Self-assessments and motion sensors (movisens: ECG-Move 4 and Move 4; Garmin: Vivosmart4) were used to record mobilization parameter from surgery to postoperative day 3 (POD3): Time out of bed, time on feet and step count. Results: 97 patients were screened and 60 included for study participation. Self-assessment showed a median out of bed duration of 215 min/day (POD1: 135 min, POD2: 225 min, POD3: 225 min). The goal of 360 min was achieved by 16.67% at POD1, 21.28% at POD2 and 20.45% at POD3. Median time on feet objectively measured by Move 4 was 109 min/day. During self-assessment, patients significantly underestimated their “time on feet”-duration with 85 min/day (p = 0.008). Median number of steps was 933/day (Move 4).Conclusion: This study confirmed with objectively supported data, that most patients don’t reach the daily mobilization goal of 360 min despite being treated by an ERAS®-pathway with ERAS®-nurse. Even considering an empirically approximated underestimation, the ERAS®-target isn’t achieved by more than 75% of patients. Therefore, we propose an adjustment of the general ERAS®-goals into more patient-centered, individualized and achievable goals. Registration: This study is part of the MINT-ERAS-project and was registered prospectively in the German Clinical Trials Register on 25.02.2022. Trial registration number is “DRKS00027863”.
Gesehen am 19.09.2024